IS CORPORATE SOCIAL RESPONSIBILITY A TOOL USED BY COMPANIES TO ENHANCE THEIR REPUTATION OR A CONTRIBUTION TO SUSTAINABILITY? (International Journal of Innovative Technologies in Economy, 2024)
Sustainable development, corporate social responsibility and social sustainability, joint efforts for the benefit of society, reduction of carbon dioxide emissions are among the most discussed topics in modern economic literature and articles. Events, discussions and debates are held in this direction. Companies, regardless of size, join this trend and try to make CSR a major part of their strategy. The group of companies really does it and strives to take care of their employees, their families, other stakeholders and society as a whole, and does it with a true sense of social responsibility. Their only goal is to improve the social well-being of their employees, create equal, comfortable working conditions, provide social comfort in society and transmit positive energy. This can be considered an activity that has achieved its goal.On the other hand, some companies approach this work as a part of their marketing activities only to raise their reputation. Sometimes they use CSR to attract customers and partners who are sensitive to sustainable development and the environment, sometimes to increase the attractiveness of their brand, sometimes to avoid sanctions imposed by the government.The real value of CSR lies in honest intent and a long-term commitment to doing the right thing. Transparency, consistency and a focus on measurable impact are key. When businesses approach CSR with integrity, they not only improve their reputation, but also play a vital role in creating a sustainable and fair world for all.